COMPANYâS BENEFITS IN CORPORATE SOCIAL RESPONSIBILITY IN HOSPITALITY INDUSTRY - Wijaya, Aditya Suryadinata (Petra Christian University, 2014)
The application of CSR in service oriented industries like tourism, restaurant and hotel are considered important because of their direct relation with the environment or their high energy consumption. Through this thesis, author wants to encourage managers in hospitality industries to adopt CSR in its business, by giving an explanation and clearance of how company can received many benefits by applying CSR into its business. The goal of this thesis is determine a real connection between implementation of CSR and companyâs benefits. In order for company to gain these benefits, managers need to ponder some considerations to pursue a better companyâs future performance. In this thesis writer will use literature review method to gather all necessary data that can help determine the relationship of CSR implementation and companyâs benefits